Evolutionary design of combinational logic circuits - Reis, Cecília (2019)
This paper proposes a genetic algorithm for designing combinational logic circuits and studies four different case examples: 2-to-1 multiplexer, one-bit full adder, four-bit parity checker and a two-bit multiplier. The objective of this work is to generate a functional circuit with the minium number of gates.